Introduction of Resource-Based Learning Disciplines of Computer Cycles in Agrarian College - Nataliia Kononets (Pedagogical Discourse, 2014)
The article focused on the issue of implementation of resource-based learning courses in the agricultural cycle computer college. Tested approach to creating e-learning resources through free hosting and their further use in the classroom. It is mentioned that the use of the Internet technology makes it possible to create educational environment of agrarian college through the development and placing electronic educational resources on the Web, because the Internet is constantly expanding its capabilities, services, hosted with their help information that is relevant in terms of education.